Relationship between Serum Cytokeratin-18, Control Attenuation Parameter, NAFLD Fibrosis Score, and Liver Steatosis in Nonalcoholic Fatty Liver Disease - Kosasih, S; Qin, WZ; Rani, RA; Abd Hamid, N; Soon, NC; Shah, SA; Yaakob, Y; Ali, RAR (Hindawi Ltd, 2024)
Backgrounds. The aim of this study was to appraise the relationship between serum fragmented cytokeratin-18(CK-18), controlled attenuation parameter (CAP), and liver steatosis assessed by ultrasound (US) in nonalcoholic fatty liver disease (NAFLD) patients. Methods. Patients who underwent abdominal US were recruited, followed with measurement of CAP using Fibroscan 5 and serum fragmented CK-18 using enzyme-linked immunosorbent assay. The degree of liver steatosis assessed by US was categorized into mild (S1), moderate (S2), and severe (S3). Results. A total of 109 patients were included in our study. CAP and fragmented CK-18 level were significantly correlated with liver steatosis grade with r(s) = 0.56 and 0.68, p=0.001, respectively. NAFLD Fibrosis Score was poorly correlated with liver steatosis grade (r(s)=-0.096, p=0.318). Using fragmented CK-18 level, area under receiver operating characteristic (AUROC) curves for S >= 2 and S >= 3 were excellent (0.82 and 0.84, respectively). Using CAP, AUROC curves for detection of S >= 2 and S >= 3 were good (0.76, 0.77, respectively). We also proposed cut-off value of CAP to detect S >= 2 and S >= 3 to be 263 and 319 db/m, respectively, and fragmented CK-18 level to detect S >= 2 and S >= 3 (194 and 294 U/L, respectively). Conclusions. Both the fragmented CK-18 level and the CAP, but not NAFLD Fibrosis Score, were well correlated with hepatic steatosis grade as assessed by US.